2010
DOI: 10.1007/s00383-010-2649-7
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of laryngotracheal separation in the treatment of severe motor and intellectual disabilities

Abstract: Intractable aspiration is a life-threatening medical problem in patients with severe motor and intellectual disabilities (SMID). Laryngotracheal separation (LTS) is a surgical procedure for the treatment of intractable aspiration which separates the upper respiratory tract from the digestive tract. We performed LTS for 14 patients with SMID to prevent intractable aspiration, performing two types of operation. The standard diversion procedure connected the upper trachea to the esophagus. The modified diversion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 15 publications
0
19
1
Order By: Relevance
“…However, in these patients immunological work-up is often not performed because an immunodeficiency is not suspected. The infections are often ascribed to food and saliva aspiration [ 1 ], structural abnormalities of the upper respiratory tract, neuromuscular problems, malnutrition or institutionalization. Besides, other problems are often more prominent than the recurrent infections.…”
Section: Introductionmentioning
confidence: 99%
“…However, in these patients immunological work-up is often not performed because an immunodeficiency is not suspected. The infections are often ascribed to food and saliva aspiration [ 1 ], structural abnormalities of the upper respiratory tract, neuromuscular problems, malnutrition or institutionalization. Besides, other problems are often more prominent than the recurrent infections.…”
Section: Introductionmentioning
confidence: 99%
“…Recurrent respiratory infections are frequently seen in patients with mental retardation and they are a major cause of mortality in this patient group. The infections are often attributed to food and saliva aspiration (1). Moreover, in many patients, structural abnormalities of the palate, tongue or oesophagus, neuromuscular problems such as cerebral palsy, and factors like malnutrition or gastro‐oesophageal reflux lead to swallowing dysfunction and aspiration, with concomitant recurrent respiratory infections (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…In the bleeding group, 3 (1 male) children had major bleeding at mean age 10.3 (range, [4][5][6][7][8][9][10][11][12][13][14][15][16] years. This occurred at a mean time of 3.6 (range, 1-5) years after LTS.…”
Section: Resultsmentioning
confidence: 99%
“…The major risk factors contributing to the formation of the TIF are (1) a low tracheostomy, (2) overinflated cuffs, and (3) thoracic deformities such as scoliosis [15,16]. The last factor, scoliosis, is a characteristic finding in children with severe mental and physical disabilities, resulting in the trachea being shifted closer to the sternum, compressing the innominate artery [7]. Our experience suggested that there should be least 2 cm between the dorsal edge of sternum and the ventral edge of vertebrate to prevent TIF.…”
Section: Discussionmentioning
confidence: 99%